أثر الرضا الوظيفي على أداء معلمي المدارس الثانوية في اليمن: The Impact of : Job Satisfaction on the Performance of Secondary School Teachers in Yemen - Abdellah Al-gailani, Amin; Abdulmalak Al-hidabi, Dawood (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2025)
ملخص البحث للمؤسسات التعليمية دور أساسي ذو تأثير كبير في تطوير المجتمع، ويُمثل المعلمون فيها عَصبَ العملية التعليمية وأساسها؛ وذلك يدعو إلى الاهتمام بهم؛ وتذليل العقبات التي تواجههم ليؤدوا دورهم التربوي، ومن هذا المنطلق، هدفت الدراسة الحالية إلى اختبار مدى تأثير الرضا الوظيفي بأبعاده الخمسة وهم ظروف العمل وطبيعته، والجانب المادي، والتدريب والنمو المهني، والإشراف التربوي، وبعد المكانة الاجتماعية على الأداء الوظيفي لدى معلمي المدارس الثانوية في اليمن. وقد استخدم الباحثان المنهج الوصفي المسحي الذي يعدُّ ملائمًا لطبيعة هذه الدراسة وأهدافها، كما اعتمد الباحثان الاستبانة بوصفها أداةً لجمع البيانات وذلك من خلال تطبيقها على عينة عشوائية مكونة من (408) معلمًا ومعلمة، للعام الدراسي2023/2024م. ولمعالجة بيانات البحث استخدم برنامج الرزم الإحصائية للعلوم الإنسانية (SPSS)، وكشفت نتائج الدراسة عن وجود علاقة إيجابية للرضا الوظيفي بأبعاده الخمسة على الأداء الوظيفي، وفي ضوء تلك النتائج تضمن البحث جملة من التوصيات للقائمين على النظام التعليمي اليمني عمومًا، ، أهمها ضرورة تقديم الرعاية المناسبة والدعم الكامل للمعلمين في المدارس الحكومية في الجمهورية اليمنية لدورهم في تنمية المجتمع والارتقاء به، حيث إن المعلم يعتبر اللبنة الأساسية للنهوض بالأجيال من خلال دوره المهم والفعال، تقديراً لجهود المعلمين من خلال تحفيزهم مادياً ومعنوياً، مما يؤدي إلى تحسين أداؤهم الوظيفي. ABSTRACT Teachers play a key role in the educational process, and therefore it is important to give them attention so that they perform their pedagogical role. Hence the current study aims to examine the influence of job satisfaction with its five dimensions: working conditions and nature, physical aspect, training and professional development, educational supervision, and social position on job performance of secondary school teachers in Yemen. The researcher adopted the descriptive method utilizing a survey which is appropriate for the nature and objectives of the current study. Moreover, the researcher used a questionnaire as a data collection instrument and applied it on the random sample that consists of 408 male and female teachers in secondary schools for the academic year 2023/2024 in Yemen. The results showed a positive relationship between job satisfaction with its five dimensions on job performance. Based on the study's findings, the researcher provided several recommendations for educational officials in Yemen. The most significant of these recommendations is the need to ensure adequate support and attention for teachers in government schools, in alignment with their critical role in societal development. Teachers play an essential role in shaping future generations. Recognizing their efforts through financial and moral incentives can significantly enhance their job performance.